Optimalisasi Pemberdayaan Laboratorium IPA dalam Upaya Meningkatkan Pemahaman Konsep-konsep Fisika bagi Guru IPA dan Siswa di Madrasah Aliyah - Rajibussalim, Rajibussalim; Yufita, Evi; Zulfalina, Zulfalina; Abdullah, Faisal; Maimun, Teuku (PESARE: Jurnal Pengabdian Sains dan Rekayasa, 2023)
A Science Laboratory at Senior High School is an important facility for students in learning Sciences, Technology, Engineering and Mathematics (STEM). Students learn concepts in the classroom and should be able to test and/or prove those concepts in experiments in Science Lab. However, many Science laboratories at schools were not fully operated due to the lack of skillful teachers or lab assistants who can manage Science laboratories with the highest standard and be able to conduct experiments with available KITs in those laboratries. Based on this phenomenon, a group of lecturers from Physics Department of Syiah Kuala University conducted a community service at school in order to share insights and skills related to a good practice in Laboratory management and demonstated how to run Physics experiments with available KITs at a designated school laboratory. The participants of this event were Science teachers and students at the school. Some of the outcomes of this community service are the increase in Laboratory management skills among science teachers at this school and increase in ability to utilise available Science KITs at that school for Physics experiments. The teachers and students were very happy and antusias to participate in this program and be benefited from this activity